2011
DOI: 10.1007/s12650-011-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

Entrained droplets in underexpanded gas jet in water

Abstract: A visualization study was performed to investigate the flow of an underexpanded nitrogen gas jet injected into water. The stagnation pressure was varied in the range 0.5-8.0 MPa. The gas jet length and expansion angle were obtained from time-averaged images captured using a high-speed camera. The gas jet length and expansion angle increased approximately linearly with increasing stagnation pressure. The entrainment velocity and the velocity of entrained water droplets in the gas jet were obtained by particle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…For void fraction measurements of the entrained water droplets into submerged gas jets, Loth and Faeth [Loth, 1989;Loth 1990] measured the local void fraction distribution and static pressure distribution of underexpanded jets submerged in water. Someya et al [Someya, 2011] investigated the spread angle and entrained droplet velocities of submerged gaseous jets and the velocity distribution of ambient water using their own visualization method. For diameter determination of entrained water droplets, several authors proposed empirical expressions which correlate droplets sizes with dimensionless numbers, even though all these correlations has been developed under aerodynamic break-up conditions ("free" droplets suddenly exposed to a high speed gas stream) or in annular flow (thin liquid film flowing on the pipe wall and a high velocity gas core flowing in its center, which carries the entrained liquid droplets).…”
Section: Submerged Gaseous Jetsmentioning
confidence: 99%
See 4 more Smart Citations
“…For void fraction measurements of the entrained water droplets into submerged gas jets, Loth and Faeth [Loth, 1989;Loth 1990] measured the local void fraction distribution and static pressure distribution of underexpanded jets submerged in water. Someya et al [Someya, 2011] investigated the spread angle and entrained droplet velocities of submerged gaseous jets and the velocity distribution of ambient water using their own visualization method. For diameter determination of entrained water droplets, several authors proposed empirical expressions which correlate droplets sizes with dimensionless numbers, even though all these correlations has been developed under aerodynamic break-up conditions ("free" droplets suddenly exposed to a high speed gas stream) or in annular flow (thin liquid film flowing on the pipe wall and a high velocity gas core flowing in its center, which carries the entrained liquid droplets).…”
Section: Submerged Gaseous Jetsmentioning
confidence: 99%
“…Someya et al [Someya, 2011] investigated horizontal submerged gas jets. They found that a jet large expansion occurred rapidly and extended about 3 mm from the inlet point; then, expansion progresses at a slower rate (i.e., a narrower angle).…”
Section: The Expansion Anglementioning
confidence: 99%
See 3 more Smart Citations